Polishness as entrance ticket and barrier to an altered labour market in the Danish construction industry. (1st April 2015) - ,
Abstract : Nationality was of very limited importance in the Scandinavian labour market during most of the 20th Century, as was also the case for other 'identities' such as ethnicity or religion. The labour movement and the workers' unions possessed immense influence over the supply of labour and were able to prevent the uncontrolled influx of workers and maintain union membership as the only prerequisite for employment. Thus the few immigrant workers in the labour market became internalised in the existing union system and worked under the same general conditions as other workers. Following the collapse of the Eastern bloc and the success of a neoliberal political and economic regime, this state of affairs has altered fundamentally. One consequence of this has been a revitalisation of nationality as a distinguishing marker. Taking its point of departure from ongoing research on Polish migrant workers in Denmark, this paper shows how nationality has become a means to gain access to the Danish labour market, mainly through the willingness to accept a lower wage. A reduction in pay also takes place when new workers are contracted within the Danish labour market system, previously renowned for its egalitarianism. The paper discusses how this apparent dilemma can be understood and whether it might be an unavoidable outcome of the transformations that have taken place on the labour markets in the new economic and political landscape.